2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1617036
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Arousals in Patients with Respiratory Sleep Disorders Using a Single Channel EEG

Abstract: Frequent arousals during sleep degrade the quality of sleep and result in sleep fragmentation. Visual inspection of physiological signals to detect the arousal events is inconvenient and time-consuming work. The purpose of this study was to develop an automatic algorithm to detect the arousal events. We proposed the automatic method to detect arousals based on time-frequency analysis and the support vector machine (SVM) classifier using a single channel sleep electroencephalogram (EEG). The performance of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…Sensitivity and precision values vary on these studies (0.42-1.00 and 0.57-1.00, respectively) as well as it does the number of PSGs involved (from 2 to 8). Is to be remarked that, at least for the approximations of Zamora and Tarassenko [5], Pacheco and Vaz [3], and Cho et al [6], the validation was limited to partial preselected periods out of the total recording time. In the work of De Carli et al [4] the standard reference was obtained from the consensus of two human scorers and their own proposed method, which might bias the result.…”
Section: Inter-scorer Variability Reported In the Literaturementioning
confidence: 99%
“…Sensitivity and precision values vary on these studies (0.42-1.00 and 0.57-1.00, respectively) as well as it does the number of PSGs involved (from 2 to 8). Is to be remarked that, at least for the approximations of Zamora and Tarassenko [5], Pacheco and Vaz [3], and Cho et al [6], the validation was limited to partial preselected periods out of the total recording time. In the work of De Carli et al [4] the standard reference was obtained from the consensus of two human scorers and their own proposed method, which might bias the result.…”
Section: Inter-scorer Variability Reported In the Literaturementioning
confidence: 99%
“…The classification was done using ANN,with weights updated using gradient descent rule. S. P. Cho et al [7] used single EEG channel time frequency features with SVM classifier and reported a sensitivity of 87.92% and specificity of 95.56 % for the training sets, and sensitivity of 75.26 % and specificity of 93.08 % for the testing sets but the results do not seem to be consistent across recordings and there is a large difference between recorded detection of positive and negative arousals. Not only this but the single channel approach is not useful for REM arousal detection as per AASM manual.…”
Section: Classification and Resultsmentioning
confidence: 99%
“…This task of visual recognition of Arousal events has some subjectivity embedded within it [5] and also a huge manual work associated which necessitates the need for objective automation. Some of the early works in this area [6] and [7] have used single channel EEGs to track the arousal events in sleep. But there is a simultaneous changes in all the channels during the time of arousal identification and when we consider only a single channel for the analysis, we miss out information from the signals of other channels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 2018 PhysioNet/ Computing in Cardiology Challenge (henceforth referred to as "Challenge") seeks to detect non-apnea arousals during sleep using a variety of physiological signals collected during polysomnographic sleep studies [3]. A limited number of approaches for detecting sleep arousal using mainly electroencephalography (EEG), electrooculography (EOG), electromyography (EMG) and electrocardiology (EKG) already exists, such as applying wavelet analysis [4], time-frequency analysis and the support vector machine (SVM) classifier [5,6] for the automatic detection of arousals during sleep.…”
Section: Introductionmentioning
confidence: 99%